Shift work organization on nurse injuries: A scoping review. (February 2023) - Imes, Christopher C.; Barthel, Nicole J.; Chasens, Eileen R.; Dunbar-Jacob, Jacqueline; Engberg, Sandra J.; Feeley, Christine A.; Fennimore, Laura A.; Godzik, Cassandra M.; Klem, Mary Lou; Luyster, Faith S.; Ren, Dianxu; Baniak, Lynn
Abstract: Background: Extended work hours and shift work can result in mistimed sleep, excessive sleepiness, and fatigue, which affects concentration and cognition. Impaired concentration and cognition negatively affect employee safety. Objective: To examine the evidence of the impact of shift work organization, specifically work hours and scheduling, on nurse injuries including needlestick and sharps injuries, drowsy driving and motor vehicle crashes, and work-related accidents causing a near miss or actual injury to the nurse. Methods: A scoping review was conducted using search results from five bibliographic databases. Results: Through database searching, 7788 articles were identified. During the title and abstract screening, 5475 articles were excluded. Full text screening eliminated 1971 articles. During the data extraction phase, 206 articles were excluded leaving 34 articles from 14 countries in the scoping review. The results of the review suggest a strong association in nurses between long work hours and overtime and an increased risk for needlestick and sharps injuries, drowsy driving and motor vehicle crashes, and other work-related accidents. Rotating shifts increase the risk for needlestick and sharps injuries and other work-related accidents while night and rotating shifts increase the risk for drowsy driving and motor vehicle crashes. Conclusions: Proper management of work hours and scheduling is essential to maximize recovery time and reduce or prevent nurse injuries. Nurse leaders, administrators, and managers, have a responsibility to create a culture of safety. This begins with safe scheduling practices, closely monitoring for near miss and actual nurse injuries, and implementing evidence-based practice strategies to reduce these occurrences.